PENGARUH KONSENTRASI ASAM ASETAT DAN WAKTU EKSTRAKSI TERHADAP MUTU KOLAGEN KULIT NILA HITAMPENGARUH KONSENTRASI ASAM ASETAT DAN WAKTU EKSTRAKSI TERHADAP MUTU KOLAGEN KULIT NILA HITAM - Latif Sahubawa; A.B. Naro Putra (Jurnal Teknosains, 2011)
The objective of the research was studied the effect of  acetic acid concentration and extraction time on the collagen quality of black tilapia leather. Black tilapia leather processed into collagen  as an alternative to increasing value-added of fisheries industry waste. Collagen of black tilapia was extracted by the treatment of acetic acid molarity, each: 0.25 M, 0.50 M, and 0.75 M (A factor) and  extraction time of 16 and 48 hours (B factor). Based on the analysis of variance, is known that the interaction of those treatments (AB) didn’t significantly effect on the yield  (p>0.05). Collagen extraction of tilapia leather with 0.75 M of acetic acid at 16 hours, produces the greatest yield  (5.97%), with denaturation temperature is 35.75oC, and quantitative composition of glisine, alanine, and glutamic amino acids were: 5395.82 ppm (52.99%), 2979.15 ppm (22.08%), and 1684.42 ppm (7.45%). Based on the analysis of SDS-PAGE, is known that the collagen contained were α component and β component, so that collagen of tilapia leather has type I collagen.